THE IMPORTANCE OF VOCABULARY IN ENGLISH LANGUAGE TEACHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Vocabulary is a fundamental component of English language teaching and plays a decisive role in learners’ ability to communicate effectively. While grammar provides the structural framework of language, vocabulary conveys meaning and enables expression. This article examines the central importance of vocabulary instruction in English language education, its influence on the development of listening, speaking, reading, and writing skills, and the psychological processes involved in lexical acquisition. The paper also analyzes modern teaching strategies, classroom techniques, and the role of technology in vocabulary development. It concludes that systematic, contextualized, and communicative vocabulary instruction is essential for successful language learning outcomes.